مظاهر العنف المدرسي كمخرجات لأبعاد المناخ المدرسي والعوامل الخمس الكبرى في الشخصية لدى طلاب المرحلة الثانوية - عاشور، أحمد حسن محمد (جامعة بنها - كلية التربية, 2014)
هدفت الدراسة بحث العلاقة بين مظاهر العنف المدرسي وأبعاد المناخ المدرسي والعوامل الخمس الكبرى في الشخصية، وتحديد التأثيرات المباشرة للمتغيرات المستقلة (أبعاد المناخ المدرسي- والعوامل الخمس الكبرى في الشخصية) على المتغير التابع (مظاهر المدرسي) (اللفظي، الجسدي، الرمزي)، كما هدفت الدراسة إلى التوصل إلى نموذج بنائي يفسر طبيعة العلاقة بين متغيرات البحث، بلغت العينة في مجملها (264) من طلاب المرحلة الثانوية العامة طبق عليهم مقياس مظاهر العنف المدرسي ومقياس المناخ المدرسي إعداد الباحث وقائمة العوامل الخمس الكبرى في الشخصية من إعداد كوستا وماكري (Costa & Mc Crae,1992) ترجمة وتقنين الأنصاري (1997) بعد التأكد من صدقهم وثباتهم. وبعد تحليل النتائج أظهرت أنه توجد علاقة ارتباطيه ودالة إحصائيا بين بعض أبعاد المناخ المدرسي ومظاهر العنف المدرسي وكذلك توجد علاقة ارتباطيه دالة إحصائيا بين بعض العوامل الخمس الكبرى في الشخصية ومظاهر العنف المدرسي، باستخدام تحليل المسار أظهرت النتائج أن بعض أبعاد المناخ المدرسي والعوامل الخمس الكبرى في الشخصية تؤثر بصورة مباشرة في مظاهر العنف المدرسي. وأخيرا تم التوصل إلى نموذج بنائي يفسر طبيعة العلاقة متغيرات البحث وتم مناقشة النتائج في ضوء أدبيات البحث وتقديم بعض التوصيات التربوية. The study aimed to explore the relationship among the school violence aspects, the school climate dimensions and the big five personality factors, it determines the direct effects of the independent variables (the school climate dimensions and the big five personality factors) on the dependent variables (the school violence aspects) (verbal, physical, symbolic).Also the research aimed to achieve a constructive model that explains the nature of the relationship between the variables of the research .The whole sample reached (246) of the secondary school students. The school violence aspects and the school climate measurements are applied on them, prepared by the researcher, and a list of the big five personality factors, prepared by Costa and Me crea (Costa& Me crea,1992) Translated and legalized by Al-Ansari (1997). After the confirmation of their validity and reliability and after the analysis of the results, they show that there is correlation and statistically significant relationship among some of school climate dimensions and the school violence aspects and there is also a correlation and statistically significant relationship between the big five personality factors and the school violence aspects. By using path analysis, the results showed that some of the dimensions of the school climate and the big five personality factors directly affect the school violence aspects. Finally we reached to a constructive model explains the nature of the relationship between the research variables .The research results have been discussed in the light of the research literature and some educational recommendations have been introduced.
Keywords: البيئة التعليمية -- الشخصية -- طلاب المرحلة الثانوية -- العنف المدرسي